Clinical evaluation, imaging studies, indications for cytologic study, and preprocedural requirements for duct brushing studies and pancreatic FNA: The papanicolaou society of cytopathology recommendations for pancreatic and biliary cytology. Issue 4 (19th February 2014) - Adler, Douglas; Max Schmidt, C.; Al‐Haddad, Mohammad; Barthel, James S.; Ljung, Britt‐Marie; Merchant, Nipun B.; Romagnuolo, Joseph; Shaaban, Akram M.; Simeone, Diane; Bishop Pitman, Martha; Field, Andrew; Layfield, Lester J.; et al.
<x xml:space="preserve">Abstract</x> The Papanicolaou Society of Cytopathology has developed a set of guidelines for pancreaticobiliary cytology including indications for endoscopic ultrasound (EUS) and fine‐needle aspiration (FNA) biopsy, techniques for EUS‐FNA, terminology and nomenclature to be used for pancreaticobiliary disease, ancillary testing, and post‐biopsy management. All documents are based on expertise of the authors, literature review, discussions of the draft document at national and international meetings, and synthesis of online comments of the draft document. This document selectively presents the results of these discussions. This document summarizes recommendations for the clinical and imaging work‐up of pancreatic and biliary tract lesions along with indications for cytologic study of these lesions. Prebrushing and FNA requirements are also discussed. Diagn. Cytopathol. 2014;42:325–332. © 2014 Wiley Periodicals, Inc.